2016
DOI: 10.1136/bmjgh-2016-000125
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to antiretroviral therapy among HIV-positive adults in sub-Saharan Africa: a systematic review

Abstract: ObjectiveThe rapid scale up of antiretroviral treatment (ART) in sub-Saharan Africa (SSA) has resulted in an increased focus on patient adherence. Non-adherence can lead to drug-resistant HIV caused by failure to achieve maximal viral suppression. Optimal treatment requires the identification of patients at high risk of suboptimal adherence and targeted interventions. The aim of this review was to identify and summarise determinants of adherence to ART among HIV-positive adults.DesignSystematic review of adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
246
4
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(286 citation statements)
references
References 184 publications
(567 reference statements)
31
246
4
5
Order By: Relevance
“…This study echoes many of the findings in the above countries which revealed how low adherence to antiretroviral therapy was related to several other significant factors: fear of HIV disclosure [50, 51]; stigma and discrimination; side effects of antiretroviral drugs [49, 52]; transportation costs; and long waiting periods at health facilities to obtain antiretroviral drugs [48, 53, 54]. A further factor was the inadequate use of modern contraceptives.…”
Section: Discussionsupporting
confidence: 79%
“…This study echoes many of the findings in the above countries which revealed how low adherence to antiretroviral therapy was related to several other significant factors: fear of HIV disclosure [50, 51]; stigma and discrimination; side effects of antiretroviral drugs [49, 52]; transportation costs; and long waiting periods at health facilities to obtain antiretroviral drugs [48, 53, 54]. A further factor was the inadequate use of modern contraceptives.…”
Section: Discussionsupporting
confidence: 79%
“…There are almost twice as many women (compared with men) on ART in SA, [15] and women have higher rates of adherence to ART. [15,16] Our patients all had considerable (asymptomatic) exposure to ART prior to presentation (although this varied widely from 5 months to 4 years), qualifying our defini tion of 'late-onset' EFV toxicity. Our patients had all recently been commenced on INH (either in the form of prophylaxis or as part of TB treatment) with an average of 3 months' INH use prior to symptom onset.…”
Section: In Practicementioning
confidence: 70%
“…High levels of adherence to ART are needed to prevent virologic failure, the development and spread of drug-resistant strains of HIV, and to achieve viral suppression (Simoni et al 2006), which is necessary to prevent the spread of HIV to uninfected partners (Rodger et al 2014). However, in sub-Saharan Africa, adherence is suboptimal with estimates of 72.9% (Heestermans et al 2016). Greater attention to adherence is critical given the shift towards a ‘test and treat’ approach (WHO 2015)—which will dramatically increase the number of individuals on ART.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by qualitative studies showing that fears around IPV limit partner disclosure, and that disclosure can trigger new incidents of violence (Colombini, James, and Ndwiga 2016, Mulrenan et al 2015). At the individual level, psychosocial and behavioral factors such as negative beliefs about HIV treatment, alcohol use, and depression have been associated with suboptimal adherence (Kagee et al 2011, Nozaki et al 2013, Nakimuli-Mpungu et al 2012, Dahab et al 2008, Heestermans et al 2016). …”
Section: Introductionmentioning
confidence: 99%